2017
DOI: 10.1002/lt.24721
|View full text |Cite
|
Sign up to set email alerts
|

Postreperfusion microcirculatory derangements after liver transplantation: Relationship to hemodynamics, serum mediators, and outcome

Abstract: Despite the growing data supporting the role of microcirculation in regulating liver function, little of this knowledge has been translated into clinical practice. The aim of this study is to quantify hepatic microcirculation in vivo using sidestream dark field (SDF) imaging and correlate these findings with hepatic blood flow, hemodynamic parameters, and soluble mediators. Postreperfusion hepatic microcirculation was assessed using SDF imaging. Hepatic microcirculation measurements included functional sinusoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
1
15
1
Order By: Relevance
“…Logistic regression analysis shows that ET‐1 and IL18 levels were independently associated with AKI. We have previously demonstrated that ET‐1 serum levels correlate with hepatic microcirculation dysfunction after reperfusion in LT . In addition to its role in IRI of the liver, ET‐1 is also an important mediator of renal physiology .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Logistic regression analysis shows that ET‐1 and IL18 levels were independently associated with AKI. We have previously demonstrated that ET‐1 serum levels correlate with hepatic microcirculation dysfunction after reperfusion in LT . In addition to its role in IRI of the liver, ET‐1 is also an important mediator of renal physiology .…”
Section: Discussionmentioning
confidence: 99%
“…(13) Logistic regression analysis shows that ET-1 and IL18 levels were independently associated with AKI. We have previously demonstrated that ET-1 serum levels correlate with hepatic microcirculation dysfunction after reperfusion in LT. (14) In addition to its role in IRI of the liver, ET-1 is also an important mediator of renal physiology. (15) Experimental studies have shown that ET-1 causes marked and prolonged renal vasoconstriction, manifested by profound reduction in renal blood flow and glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Free reactive oxygen species are responsible for tissue injury but also for the amplification of this phenomenon. Further, liver ischemia‐reperfusion injury is characterized by alteration of the microcirculation . Platelets were shown to play a key role in this process.…”
Section: Ischemia‐reperfusion Injurymentioning
confidence: 99%
“…Further, liver ischemia-reperfusion injury is characterized by alteration of the microcirculation. (106,107) Platelets were shown to play a key role in this process. First, platelets aggregate within sinusoids during the ischemic phase, contributing to the propagation of no-reflow zones during reperfusion.…”
Section: Ischemia-reperfusion Injurymentioning
confidence: 99%